The Impact of Investment, Inflation, and Productive Zakat on the Welfare of People in Medan - Aji, Mhd. Habrul; Imsar, Imsar; Daulay, Aqwa Naser (PT Mattawang Mediatama Solution, 2024)
This study aims to analyze the impact of Investment, Inflation, and Productive Zakat on the Welfare of the Community in Medan City. The research employed a quantitative method using Ordinary Least Squares (OLS) regression. Secondary data from BPS, BAZNAZ National, and PNM Medan for the period 2018-2023 were utilized. Data analysis involved multiple linear regression models supported by classic assumption tests, conducted using Eviews version 12. The results indicate that investment and productive zakat have a positive and significant influence on the welfare of the community in Medan City from 2018 to 2023. However, inflation negatively and significantly affects community welfare during the same period. Future research should consider integrating other economic factors such as per capita income, income distribution, and social inequality.